(NmUZYKAL_NYJ SOWREMENNIK (B.s (NSBORNIK STATEJ wYPUSK (B6s - (Nr(B.(N{AWERDQNs (NREDAKTORs ((NmOSKWAs (NsOW(B.(NKOMPOZITORs, 1987)
(NpREDLAGAEMYJ WNIMANI@ ^ITATELEJ [ESTOJ WYPUSK SBORNIKA mUZYKAL_NYJ SOWREMENNIK W OSNOWNOMSODERVIT STAT_I(B.s
Keywords: (NISTORIQs